Characteristics and Clinical Outcomes of Patients Referred to a Cardio-Oncology Clinic: The First Lebanese Experience - Fakhreddine, Omar; Alameh, Ibrahim; Atoui, Ali; Taher, Ali; Bazarbachi, Ali; Skouri, Hadi (Cardiology and Cardiovascular Medicine, 2024)
Introduction: Survival rates in cancer patients have improved dramatically in the past ten years, especially with the discovery of novel cancer therapy which was found to be associated with multiple cardiovascular complications. The development of cardio oncology clinics has evolved in order to address this issue. Objectives: This study is aimed to report the characteristics and clinical outcomes of patients presenting to our cardio oncology clinic in order to improve the care for this patient population. Material and Methods: Hematologic and solid malignancy patients referred to the cardio oncology clinic at the American University of Beirut Medical Center will be included in this study. Results: Of the 119 patients, the median age was 59, and 57% were women. The most common reason for referral was pre-therapy assessment. After a follow up period of 12 months, 55% of the patients who had a drop in their LVEF achieved full recovery, 22.5% experienced partial improvement. 55% of the patients completed their chemotherapy regimen where 8% had discontinued the treatment at some point. 83% of patients were alive at the end of follow up, 17% died with septic shock being the most common cause. Conclusion: Despite challenges, the COC demonstrated significant success in managing patients at risk or with known cardiovascular comorbidities who are being treated for cancer, emphasizing the importance of multidisciplinary care. These findings underscore the importance of specialized cardiac care within the realm of oncology and emphasize the need for early risk stratification, early preventive measures, and continued research to optimize the management of cardiovascular health in cancer patients.